An Immunomodulatory Hydrogel Featuring Antibacterial and Reactive Oxygen Species Scavenging Properties for Treating Periodontitis in Diabetes - Ge, Xinxin (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.